Regenerating Liverpool Pier Head waterfront: the role of urban design - Fageir, Mohamed; Porter, Nicole; Borsi, Katharina (MacroWorld, 2015)
This paper investigates the processes by which the regeneration of the historical Pier Head waterfront in Liverpool took place during the first decade of the twenty-first century. The research focuses on three key regeneration projects at Pier Head Waterfront, namely the Fourth Grace, the New Museum of Liverpool and Mann Island Development. Each of these projects has undergone a relatively different process and, hence, faced different challenges and produced different outcomes. This study is based on a series of lengthy interviews with key stakeholders closely linked with the regeneration of the waterfront, a review of project related documents including urban design policy and guidance, a substantial review of relevant news articles that were written throughout the period of the recent transformation of the waterfront, and numerous site visits. By understanding the peculiarities of the global forces that drive large scale developments and the local context in which they occurred at Pier Head, several insights regarding the process of regeneration emerge. Findings foreground the role of urban design in urban waterfront regeneration, illustrating that despite the complexity of managing change, urban design has the capacity to mediate between the local and global forces and the needs/desires of investors and local communities. Urban design is also imperative for challenging the negative impact of globalisation on the urban landscape